1996
DOI: 10.1016/s0022-5347(01)65667-2
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Epitectin (MUC-1 Glycoprotein) in the Menstrual Cycle and Interstitial Cystitis

Abstract: Decreased mean urinary epitectin levels may reflect a cause (epithelial mucin deficiency) or a consequence of interstitial cystitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…This observation indicating the presence of galectins was further substantiated by the isolation of a 30-kDa protein by af nity chromatography of rabbit bladder extracts on immobilized lactose (4). Finally, the polymerase chain reaction (PCR) 2 was used to show the expression of both galectin-3 and galectin-4 in rabbit epithelium (unpublished data). Galectins are a family of animal lectins that ful ll two criteria: af nity for b -galactoside sugars, and shared characteristic amino acid sequences (5)(6)(7)(8).…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…This observation indicating the presence of galectins was further substantiated by the isolation of a 30-kDa protein by af nity chromatography of rabbit bladder extracts on immobilized lactose (4). Finally, the polymerase chain reaction (PCR) 2 was used to show the expression of both galectin-3 and galectin-4 in rabbit epithelium (unpublished data). Galectins are a family of animal lectins that ful ll two criteria: af nity for b -galactoside sugars, and shared characteristic amino acid sequences (5)(6)(7)(8).…”
Section: Introductionmentioning
confidence: 89%
“…We are investigating the role of bladder epithelial glycoconjugates in bladder disorders such as interstitial cystitis (1)(2)(3). In continuation of these studies, histochemical examination of rabbit and human bladder sections revealed strong calcium-independent binding of b -Dgalactose neoglycoconjugates (4).…”
Section: Introductionmentioning
confidence: 99%